Book review - Sebestyén, Krisztina (International Dialogues on Education Journal, 2021)
As researchers, we know that we cannot examine a phenomenon or a process alone, we should study the environment or other phenomena, which are connected to the topic of research. This is true of educational processes too and this is the reason why education is examined e. g. from economic, social, or territorial views. Roland Hegedűs’s book on the topic of the performance of disadvantaged and non-disadvantaged students and the territorial perspective of their studies in secondary education and in higher education can be found in this research field.